2017
DOI: 10.2147/ott.s130055
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin exerts its antitumor activity through regulation of miR-7/Skp2/p21 in nasopharyngeal carcinoma cells

Abstract: Curcumin, a natural polyphenol compound, exhibits tumor suppressive activity in a wide spectrum of cancers, including nasopharyngeal carcinoma cells. However, the exact molecular mechanisms governing this tumor suppressive activity remain elusive. Multiple studies have revealed that miRNAs are critically involved in tumorigenesis, indicating that targeting miRNAs could be a therapeutic strategy for treating human cancer. In the current study, we set out to determine whether curcumin regulates miR-7 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 61 publications
(71 reference statements)
2
29
0
1
Order By: Relevance
“…Simvastatin, an HMG-Co-enzyme A reductase inhibitor, induced cell cycle arrest via suppression of the STAT3/Skp2 axis in order to promote p27 and p21 accumulation in liver carcinoma cells (37). Curcumin has been demonstrated to inhibit the expression of Skp2 in several human cancer types (17,38,39). Rottlerin exhibited its anti-tumor activity by the inhibition of Skp2 in breast cancer and pancreatic cancer cells (18,40).…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin, an HMG-Co-enzyme A reductase inhibitor, induced cell cycle arrest via suppression of the STAT3/Skp2 axis in order to promote p27 and p21 accumulation in liver carcinoma cells (37). Curcumin has been demonstrated to inhibit the expression of Skp2 in several human cancer types (17,38,39). Rottlerin exhibited its anti-tumor activity by the inhibition of Skp2 in breast cancer and pancreatic cancer cells (18,40).…”
Section: Discussionmentioning
confidence: 99%
“…4F). Although it is still in the early stages for our understanding of the regulatory mechanisms of individual miRNA expression, it was shown that miR-7 was increased by estrogen (Masuda et al 2012), oleic acid (Kumar et al 2017), and curcumin (Feng et al 2017) in some cancer cells, while miR-141/ 200 expression was induced by oxidative stress such as hydrogen peroxide (Magenta et al 2011;Mateescu et al 2011). It is obvious that the regulation of IRP-IRE interactions by cellular iron status governs the stability of TfR1 mRNA; however, it is conceivable that expression changes in these miRNAs in response to environmental cues and in different tissues ultimately determine the stability of TfR1 mRNA and cellular iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is shown to have anticancer potential for the prevention and treatment of different cancers [ 70 , 71 ]. The underlying anticancer mechanisms of curcumin mainly depend on the inhibition of cancer cell growth, induction of cancer cell apoptosis, and suppression of cancer cell metastasis [ 70 , 72 , 73 ].…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%
“…The observation on head-neck squamous cell carcinoma (HNSCC) cells indicates that the short-term exposure of curcumin at low concentrations results in the inhibition of colony formation as well as the growth of cells [ 73 ]. In vitro studies show that the treatment with curcumin causes 65% and 55% inhibition of cell proliferation in human nasopharyngeal carcinoma cell lines, CNE1 and CNE2, respectively [ 72 ]. In addition, curcumin treatment in vivo at the doses of 1000 and 1500 mg/kg leads to a 21.03% and 35.57% inhibition of the tumor growth, respectively, compared to the group of cervical cancer implanted nude mice [ 74 ].…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%
See 1 more Smart Citation